The Evolution of Breast Satisfaction and Well-Being after Breast Cancer: A Propensity-Matched Comparison to the Norm. Issue 3 (March 2020) - Mundy, Lily R.; Rosenberger, Laura H.; Rushing, Christel N.; Atisha, Dunya; Pusic, Andrea L.; Hollenbeck, Scott T.; Hyslop, Terry; Hwang, E. Shelley
Abstract : Background: Breast cancer survival continues to improve, with women living longer after treatment. It is not well understood how long-term satisfaction and well-being differ following treatment or how types of reconstruction differ when compared to the norm. Methods: In a propensity-matched sample, the authors compared patient-reported outcomes in breast cancer patients at various time intervals from surgery with normative BREAST-Q data. All data were obtained using the Army of Women, an online community fostering breast cancer research. Breast cancer patients were stratified by surgical treatment and reconstruction type. Regression lines were estimated and differences in slope tested between cancer patients and noncancer controls. Results: The authors compared normative ( n = 922) and breast cancer ( n = 4343) cohorts in a propensity-matched analysis. Among the breast cancer patients, 49.4 percent underwent lumpectomy, 17.0 percent underwent mastectomy, 21.7 percent underwent implant reconstruction, and 11.9 percent underwent autologous reconstruction. Median time since surgery was 4.7 years, with 21.1 percent more than 10 years after surgery. At the time of survey, breast cancer patients reported higher Satisfaction with Breasts and Psychosocial Well-being scores compared to noncancer controls ( p < 0.01), with the cohorts undergoing lumpectomy and autologous reconstruction both reporting higher scores than the normative controls. After mastectomy, scores averaged lower than the noncancer controls, but improved over time. However, all breast cancer groups reported significantly lower Physical Well-being scores than the noncancer cohort (all p < 0.01). Conclusions: Breast cancer patients undergoing lumpectomy or autologous reconstruction reported higher psychosocial well-being compared to noncancer controls. These differences were influenced both by time since treatment and by choice of surgical procedure. Abstract : Supplemental Digital Content is available in the text.